2022
DOI: 10.3390/cancers14040907
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibitors and Radiometabolic Approaches in Metastatic Castration-Resistant Prostate Cancer: What’s Now, What’s New, and What’s Coming?

Abstract: In recent years, the advances in the knowledge on the molecular characteristics of prostate cancer is allowing to explore novel treatment scenarios. Furthermore, technological discoveries are widening diagnostic and treatment weapons at the clinician disposal. Among these, great relevance is being gained by PARP inhibitors and radiometabolic approaches. The result is that DNA repair genes need to be altered in a high percentage of patients with metastatic prostate cancer, making these patients optimal candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 84 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…Some trials are studying the combination of 177Lu-PSMA radioligands with PARPi [ 96 ]. Ongoing trials with this and other combination of drugs are shown in Table 4 .…”
Section: Clinical Development Of Parp Inhibitors In Prostate Cancermentioning
confidence: 99%
“…Some trials are studying the combination of 177Lu-PSMA radioligands with PARPi [ 96 ]. Ongoing trials with this and other combination of drugs are shown in Table 4 .…”
Section: Clinical Development Of Parp Inhibitors In Prostate Cancermentioning
confidence: 99%
“…Furthermore, those with BRCA1/2 alterations were particularly responsive to Olaparib when compared to other HRR gene mutations (52% vs 5% achieving a radiological response to Olaparib respectively). 46 , 47 Finally, in the randomized phase III PROfound clinical trial, the effectiveness of Olaparib was compared to being treated with enzalutamide or abiraterone in patients with mCRPC with alterations in 15 prespecified HRR genes (the mutations analyzed can be seen in Table 2 . Other than those listed, mutations in the PPP2R2A gene were examined as well).…”
Section: Comparison With Other Parp Inhibitorsmentioning
confidence: 99%
“…These results led to approvals by both the FDA and EMA for mCRPC with HRR mutations, although the EMA was more conservative in the scope of Olaparib’s approval. 37 , 46 , 47 …”
Section: Comparison With Other Parp Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations